1973
DOI: 10.1016/0017-9310(73)90033-1
|View full text |Cite
|
Sign up to set email alerts
|

Simple method of predicting friction factors of turbulent flow in non-circular channels

Abstract: Abstract-On the basis of friction factor relationships of a simple model a method is developed which allows the prediction of friction factors for turbulent flow in non-circular channels if only the geometry factor of the pressure drop relationship for laminar flow is known. The proposed method of calculation is tested with numerous experimental results from the literature with respect to non-circular channels such as triangular shaped ducts, eccentric annuli and rod bundles in hexagonal and square arrays in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…It is realized that the validity of the present analysis is hugely dependent on the correctness of the empirical correlations in predicting friction factor and heat transfer coefficients determined experimentally by Cheng and Todreas [5], Presser [8] and Weisman [9]. A common practice in subchannel pressure drop and heat transfer experiments is to compare the results with an equivalent annular zone solution as described in details in Todreas and Kazimi [47] and Rehme [1,2,48]. The equivalent annulus model as depicted in Todreas and Kazimi [47] has been shown in Fig.…”
Section: Analysis For Validation With Equivalent Annulus Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…It is realized that the validity of the present analysis is hugely dependent on the correctness of the empirical correlations in predicting friction factor and heat transfer coefficients determined experimentally by Cheng and Todreas [5], Presser [8] and Weisman [9]. A common practice in subchannel pressure drop and heat transfer experiments is to compare the results with an equivalent annular zone solution as described in details in Todreas and Kazimi [47] and Rehme [1,2,48]. The equivalent annulus model as depicted in Todreas and Kazimi [47] has been shown in Fig.…”
Section: Analysis For Validation With Equivalent Annulus Modelmentioning
confidence: 98%
“…It was concluded that the pressure drop coefficients for closely packed rod bundles deviate hugely from that for a circular pipe. Subsequently, Rehme [2] proposed a transcendental equation to predict the friction factor in various non-circular channels. Deissler and Taylor [3,4] analyzed fully developed turbulent flow and heat transfer in triangular and square arrays.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of measurement techniques, more experiments were presented in the late 1990 [4][5][6][7][8][9], which indicate that the turbulent flow in a rod bundle has completely different characteristics compared to that in a pipe. A high mixing in the gap region was observed, which was once explained by the secondary flow.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, literature covers different fluids, like gas, liquid, non-Newtonian fluids, and, recently, nanofluids [14,20,21]. An experimental approach [4,17] or analytical [22] and numerical methods [21,23,24] have been adopted. Shah and London [25] performed a huge and exhaustive review about theoretical and experimental analyses on laminar forced convection and heat transfer in noncircular ducts.…”
Section: Introductionmentioning
confidence: 99%